Career Planning and Aspirations of Bangladeshi Graduates: Analyzing Quality Education and Economic Opportunities - Sakil, Afzal Hossain (Universitas Bina Darma, 2024)
Bangladesh is an overpopulated country with a significant portion of educated youth preparing to enter their career after graduation. Mentors, family, career councilors, and societal expectations play a significant role in shaping the future career paths of youth. To conduct the research, mixed-method approach was followed. Both quantitative and qualitative methods were accumulated, where structured questionnaires were used to collect qualitative data using simple random sampling method, and FGDs were used to collect qualitative data. The findings indicates that 29% preferred career is in the public sector, and the reasons behind it are the stability of job and reputation and social value. Based on the findings, the major challenges students face are economic downturns, work-life balance concerns, geographic constraints, fear of rejection, etc. The research recommended redesigning the courses and developing skill development programme for proper implication of policy and education system. The findings of this study will help policymakers, educators, and career counsellors determine how they can guide current fresh graduates in determining their career paths. Based on the differences in the economic characteristics of Bangladesh, these results will help graduates adopt career planning strategies more systematically.